Musculoskeletal disorders among bank office workers in Kuwait. - Akrouf QA; Crawford JO; Al-Shatti AS; Kamel MI (Eastern Mediterranean Health Journal)
This cross-sectional observational study assessed the pattern of musculoskeletal disorder (MSDs) suffered by bank office workers in Kuwait. A self-administered validated questionnaire was used that included the Nordic musculoskeletal questionnaire and 12-item general health questionnaire (GHQ12). Of 750 employees, 80% suffered at least 1 episode of MSD during the previous year and 42% suffered at least 1 disabling episode. The most affected body parts were the neck (53.5%), lower back (51.1%), shoulders (49.2%) and upper back (38.4%). Nationality, GHQ12 score, smoking and sex were significant predictors of MSDs during the previous year, while alcohol drinking, marital status, GHQ12 score, years in Kuwait and sex were significant predictors of disabling MSDs during the previous year.